Effects of silver nanoparticles–polysaccharide on bleomycin-induced pulmonary fibrosis in rats. (13th September 2021) - Hassan, Amal I; Samir, Amer; Youssef, Hanan F; Mohamed, Sahar S; Asker, Mohsen S; Mahmoud, Manal G
Abstract: Objectives: The first goal of this study was to synthesize the silver nanoparticles Alcaligenes xylosoxidans exopolysaccharide (Ag-AXEPS). The second objective was to analyse the role of Ag-AXEPS nanoparticles (NPS) in treating bleomycin (BLM)-induced lung fibrosis. Methods: Intratracheal bleomycin (2.5 U/kg) was administered to prompt pulmonary fibrosis in rats, and pulmonary fibrosis was treated with Ag-AXEPS nanoparticles (100 ppm/twice a week for four weeks). Key ﬁndings: Ag-AXEPS nanoparticles significantly decreased the diversity of pulmonary inflammatory agents in rats with BLM-induced fibrosis. Reduced levels of respiratory tumor necrosis factor-alpha, monocyte chemotactic protein-1, matrix metalloproteinases (MMP-2 and MMP-9) were observed on treatment with synthesized Ag-AXEPS. Similarly, the treatment decreased IL-12, mRNA levels of BAX and plasma fibrosis markers like N-terminal procollagen III propeptide and transforming growth factor-β1. On the other hand, the treatment increased mRNA BCL2 and total antioxidant capacity. It also lowered the level of fibrosis, as was shown by a quantified pathologic study of hematoxylin–eosin-stained lung parts. The treatment, however, ensured that lung collagen was restored, as assessed by Masson's trichrome stain, and that overall survival was increased and enhanced. Conclusions: Our work showed that nanoparticles could be obtained at 37°C and may be a possible pulmonary fibrosis therapeutic agent.